Healthcare capacity strengthening in conflict settings through virtual emergency medical training and outreach: Ukraine and Sudan case studies - D’Andrea, Shawn M.; Fadul, Nada; Dery, MarkAlain; Brim, William L.; Israel, Andrea M.; Struminger, Bruce Baird (Frontiers in Public Health, 2024)
The use of digital learning in healthcare is expanding in a range of contexts including for settings of armed conflict. Humanitarian emergencies and war often lead to a surge of traumatic injuries, emotional distress, and disruption to health systems risking neglect and exacerbations of chronic illness, and acute infectious disease outbreaks, often requiring an international response. On the ground humanitarian response is often essential though logistical and security challenges can delay these responses, and the reliance on an international workforce unfamiliar with local cultures can create challenges in response efforts. In crises where local healthcare workers have limited training, or experience in emergency care, digital health care education can augment in-person response and training efforts. In recent years digital emergency care education programs have been deployed to both Ukraine and Sudan. A review of each of these programs demonstrates successes in and potential utility of remote healthcare capacity strengthening through digital education in settings of war. These programs provide important lessons in strengths of and challenges in developing and delivering just in time learning programs to settings of active armed conflict suggesting similar potential utility in a variety of humanitarian emergency contexts.